Postharvest: an unsung solution for food security - Tengku Muda Mohamed, Mahmud (Universiti Putra Malaysia Press, 2017)
In agriculture, postharvest is the last stage of crop production that spans from harvesting until the produce is being utilised by consumers. It includes handling practices involving harvesting, sorting, cleaning, pre-cooling, grading, packing, storage, transportation and postharvest treatments. The moment a produce is uprooted from the ground, or separated from the parent plant, it begins to deteriorate. To totally check this deterioration process is impossible, so the only alternative we have is to slow down the progression. Only then can we retain the quality of the produce longest possible. On the other hand, food waste, which is a subset of postharvest food losses, is the loss of edible food due to human action or inaction, such as throwing away produce, not consuming available food before its expiry date or taking serving sizes beyond one’s ability to consume. The former is related to the early stages of the food supply chain (FSC) and refers to a system which needs investment in infrastructure. Food waste is applied to later stages of the FSC and generally, relates to the attitude of food suppliers and consumers. Like it or not, food losses and wastes will influence global food security. Increasing agricultural productivity is critical for ensuring global food security, but this may not be sufficient. The methods of increasing food supply include continous increase in the production area and yields as well as producing more crops per year. However, the other aspect that is always overlooked is the reduction of postharvest losses. In light of these issues, this write-up highlights some of the causes of postharvest deterioration which are identified as lack of knowledge and information, inadequate transportation facilities, unavailability of needed tools and equipment and losses at the distribution level. Pre-harvest factors are crucial for retention of quality after harvest. All related factors, such as water stress, nutrition (calcium in particular), light exposure, temperature and salinity, have a substantial influence on the postharvest quality of a produce. Quality responses to biotic and abiotic stresses are also discussed. Various strategies and interventions that have been developed and proposed, including those from UPM, to reduce postharvest losses and improve handling, storage and transportation operations of fresh produce during the entire supply chain are also highlighted. In order to control the high magnitude of postharvest losses and food waste, plausible action must be taken to upgrade the existing systems. In the present world, where millions of people go to bed without food, it would be a crime to allow continuation of postharvest losses and food wastes.